Lithium ion battery
By embossing the positive electrode sheet of the lithium-ion battery and adjusting the electrolyte composition, the problem of lithium-ion battery excision phenomenon during fast charging of lithium-ion batteries is solved, and the safety and fast charging performance of the battery are improved.
Patent Information
- Application Number
- CN202411725083.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the fast charging process of lithium-ion batteries, lithium-ion excision phenomenon leads to reduced battery life and safety risks, and it is difficult for the prior art to effectively control and avoid this problem.
By embossing the positive electrode sheet, uneven textures are formed, and the ratio of the depression depth to the positive electrode sheet thickness, the content of boron additives and fluorovinyl carbonate in the electrolyte is adjusted to meet the specific relationship to improve the positive electrode active material The lithium embedded and deliques rate consistency, uniformity, reduce interface impedance and safety risks.
It effectively alleviates the uneven thickness of the negative electrode SEI film caused by inconsistent lithium embedded and deliquefaction rates of positive electrode active particles, reduces interface impedance, and improves the safety performance and fast charging performance of the battery.
Smart Images

Figure CN119230918A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art
[0002] Lithium-ion batteries currently dominate the portable electronic device battery market due to their high specific energy density, wide temperature range and long cycle life. With the rapid development of lithium-ion battery technology, people have put forward higher requirements for the fast charging performance and safety performance of lithium-ion batteries.
[0003] However, during the fast charging process of the battery, a problem that needs to be solved is the lithium plating phenomenon. When lithium ions are quickly deintercalated from the positive electrode and try to be embedded in the negative electrode, if the embedding speed of the negative electrode cannot keep up with the charging speed, or the surface of the electrode is saturated with lithium, lithium ions will be deposited on the surface of the negative electrode to form metallic lithium. This will not only reduce the service life of the battery, but may also cause safety problems such as battery overheating, expansion, and even fire. Therefore, how to effectively control and avoid lithium plating while increasing the charging speed has become an important issue in the development of lithium battery technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and provide a lithium ion battery. By embossing, the surface of the positive electrode sheet is formed with an uneven texture, which can improve the stress concentration of the positive electrode, and improve the structural stability of the positive electrode active material inside the positive electrode sheet and the electrolyte wettability. At the same time, by adjusting the ratio of the depth of the recessed portion to the thickness of the positive electrode sheet, and when the content of the boron-containing additive in the electrolyte and the content of fluoroethylene carbonate meet a specific relationship, the uneven texture of the positive electrode can alleviate the uneven thickness of the negative electrode SEI film caused by the inconsistent lithium insertion and delithiation rates of the positive electrode active material, so that the thickness uniformity of the negative electrode SEI film is better, the interface impedance is reduced, the interface lithium precipitation is improved, and the safety performance of the battery is improved.
[0005] In order to achieve the above object, the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side surface of the positive electrode current collector; In the thickness direction of the positive electrode sheet, the positive electrode sheet comprises a first surface and a second surface arranged opposite to each other, and at least a part of the first surface is recessed toward the second surface to form a plurality of recessed portions; and / or at least a part of the second surface is recessed toward the first surface to form a plurality of recessed portions; Wherein, the thickness of the positive electrode sheet is recorded as H μm, the depth of the recess is recorded as h μm, L=h / H, L=5%~30%; The electrolyte includes a boron-containing additive, and the mass proportion of the boron-containing additive is denoted as A% based on the total mass of the electrolyte; The electrolyte includes fluoroethylene carbonate, and the mass proportion of fluoroethylene carbonate is denoted as B% based on the total mass of the electrolyte; L, A and B satisfy the relationship: A+B≥0.15L+7.
[0006] The present invention adopts the above technical solution to achieve the following beneficial effects: The lithium-ion battery provided by the present invention forms an uneven texture on the surface of the positive electrode sheet through embossing treatment, which can improve the stress concentration of the positive electrode and improve the structural stability and electrolyte wettability of the positive electrode active material inside the positive electrode sheet. However, after the positive electrode is embossed, the lithium insertion and removal rates of the active materials in the embossed part and the unembossed part are inconsistent, resulting in inconsistent thickness of the negative electrode SEI film, which easily leads to lithium precipitation. The present invention can alleviate the unevenness of the thickness of the negative electrode SEI film caused by the inconsistent lithium insertion and removal rates of the positive electrode active particles by adjusting the ratio L of the depth of the recessed portion to the thickness of the positive electrode sheet, and adjusting the content A of the boron-containing additive and the content B of fluoroethylene carbonate in the electrolyte to meet A+B≥0.15L+7, so that the thickness of the negative electrode SEI film is more uniform, the interface impedance is reduced, the interface lithium precipitation is improved, and the safety performance of the battery is improved.
[0007] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 Shown is a schematic diagram of a top view of the positive electrode sheet in an embodiment of the present invention.
[0009] Figure 2 Shown is a schematic diagram of a cross-sectional structure (along the thickness direction of the electrode sheet) of a positive electrode sheet in an embodiment of the present invention.
[0010] Figure numerals: 1, positive electrode sheet; 2, positive electrode current collector; 3, positive electrode active material layer; 4, recessed area; 5, first surface; 6, second surface; 7, recessed portion; 8, raised portion. DETAILED DESCRIPTION
[0011] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0012] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0013] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.
[0014] In the present invention, the term "C2-C10 mononitrile compound" refers to a nitrile compound containing only one cyano group and having a carbon number between 2 and 10. The mononitrile compound includes both saturated mononitrile compounds and unsaturated mononitrile compounds.
[0015] In the present invention, the term "C2-C10 polynitrile compound" refers to a nitrile compound containing two or more cyano groups and having a carbon number between 2 and 10. The polynitrile compound includes both saturated polynitrile compounds and unsaturated polynitrile compounds.
[0016] In the present invention, the term "C4-C8 carboxylate" refers to a carboxylate in which the number of carbon atoms in the hydrocarbon group (i.e., the carbon chain connected to the carboxyl group) in the carboxylate molecule is between 4 and 8.
[0017] The present invention provides a lithium ion battery, the battery comprising a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side surface of the positive electrode current collector; In the thickness direction of the positive electrode sheet, the positive electrode sheet comprises a first surface and a second surface arranged opposite to each other, and at least a part of the first surface is recessed toward the second surface to form a plurality of recessed portions; and / or at least a part of the second surface is recessed toward the first surface to form a plurality of recessed portions; Wherein, the thickness of the positive electrode sheet is recorded as H μm, the depth of the recess is recorded as h μm, L=h / H, L=5%~30%; The electrolyte includes a boron-containing additive, and the mass proportion of the boron-containing additive is denoted as A% based on the total mass of the electrolyte; The electrolyte includes fluoroethylene carbonate, and the mass proportion of fluoroethylene carbonate is denoted as B% based on the total mass of the electrolyte; L, A and B satisfy the relationship: A+B≥0.15L+7.
[0018] It should be noted that when calculating the relationship A+B≥0.15L+7, A, B, and L are all substituted into the formula with the corresponding percentage values. For example, when L=30%, A=1%, and B=15%, the relationship is: 1+15≥0.15×30+7, that is, 16>11.5.
[0019] Exemplarily, L can be 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 29%, 30%, or any point value in the range consisting of any two of the above point values.
[0020] The present invention sets a concave portion on one surface of the positive electrode sheet through embossing, and sets a convex portion corresponding to the concave area on the other surface of the positive electrode sheet, so that the surface of the positive electrode sheet forms an uneven texture, so that the surface of the positive electrode sheet has a certain gap structure, which can improve the stress concentration of the positive electrode, and improve the structural stability and electrolyte wettability of the positive electrode active material inside the positive electrode sheet. However, after the positive electrode is embossed, fine cracks are generated in the structure of the positive electrode active material at the convex part, and the compaction density of the positive electrode active layer at the convex part is changed, resulting in inconsistent lithium insertion and delithiation rates of the positive electrode active material at the convex part and the straight section (non-convex position), thereby resulting in inconsistent thickness of the negative electrode SEI film corresponding to the convex part and the straight section, resulting in uneven distribution of lithium ion flow on the surface of the negative electrode sheet, and areas with larger lithium ion flow may form thicker SEI films, while areas with smaller lithium ion flow may form thinner SEI films. At the thicker SEI film, the charge mass transfer impedance is large, and lithium dendrites are easily formed, which aggravates the lithium precipitation phenomenon and affects the safety performance of the battery.
[0021] The present invention adjusts the ratio L of the depth of the recessed portion to the thickness of the positive electrode sheet, and adjusts the content A of the boron-containing additive and the content B of fluoroethylene carbonate in the electrolyte to satisfy A+B≥0.15L+7, so that both the boron-containing additive and the fluoroethylene carbonate have strong film-forming ability, and by increasing the mass proportion of the boron-containing additive and the fluoroethylene carbonate in the electrolyte, a side surface of a raised portion is provided after the positive electrode is embossed, the electrolyte at the position of the raised portion is less than the electrolyte at the straight section (the non-raised position), and the uneven distribution of the electrolyte leads to inconsistent contents of the boron-containing additive in the negative electrode corresponding to the raised portion and the negative electrode corresponding to the straight section; and a side surface of the recessed portion has more electrolyte in the recessed portion than in the straight section, and the uneven distribution of the electrolyte leads to inconsistent contents of the boron-containing additive in the negative electrode corresponding to the recessed portion and the straight section, so that the problem of uneven thickness of the negative electrode SEI film caused by inconsistent lithium insertion and delithiation rates of the positive electrode active material can be improved, the interface impedance can be reduced, the interface lithium precipitation can be improved, and the safety performance of the battery can be improved.
[0022] In the present invention, L, A and B satisfy the relationship: A+B>0.15L+7, which can avoid the mass proportion of boron-containing additives and fluoroethylene carbonate being too small. When the formula is not satisfied, the charge transfer impedance in the surface area of the negative electrode sheet is large, fast charging and lithium precipitation are prone to occur, and the battery cell expands greatly, which is not conducive to the cycle safety and fast charging performance of the battery; it can also avoid that when L is too large, the recessed portion is too deep, affecting the mechanical stability of the negative electrode sheet structure during the battery charging and discharging process.
[0023] In some embodiments, in the positive electrode sheet, a plurality of recessed portions are arranged in multiple rows and columns. The first protrusions and the first recessed portions may be arranged in a uniformly spaced arrangement, or the arrangement may be adjusted according to actual needs, such as partially arranged in multiple rows and columns with uniform spacing, and partially arranged in multiple rows and columns with non-uniform spacing.
[0024] In some embodiments, Figure 1 and Figure 2 As shown, the positive electrode sheet 1 includes a positive electrode current collector 2 and a positive electrode active material layer 3 arranged on both sides of the positive electrode current collector 2. The entire surface of the positive electrode sheet 1 is embossed, and the positive electrode sheet 1 includes a first surface 5 and a second surface 6 arranged opposite to each other. After the first surface 5 is embossed, in the thickness direction of the positive electrode sheet 1, a part of the first surface 5 is recessed toward the second surface 6 to form a number of evenly spaced recesses 7, and the several recesses 7 constitute a recessed area 4; the second surface 6 forms a number of evenly spaced protrusions 8 corresponding to the recesses 7. Similarly, after the second surface 6 is embossed, a number of evenly spaced recesses 7 can be formed, and a number of evenly spaced protrusions 8 corresponding to the recesses 7 can be formed on the first surface 5, that is, the positions of the protrusions 8 and the recesses 7 in the first surface 5 and the second surface 6 can be interchanged.
[0025] In some other embodiments, when the entire surface of the positive electrode sheet is embossed, embossing can also be performed on a portion of the first surface 5 of the positive electrode sheet, and embossing can be performed on another portion of the second surface 6 of the positive electrode sheet (non-embossed area), so that there are both raised portions and recessed portions in the first surface 5 and the second surface 6 of the positive electrode sheet.
[0026] In some other embodiments, the embossing process may be performed only on a local area of the positive electrode sheet, such as an edge area, an arc area, etc.
[0027] In some embodiments, the raised portion or the depressed portion (embossed pattern) is a regular or irregular shape, such as a circle, a square, a hexagon, other regular shapes or irregular shapes, preferably a regular shape, such as preferably a circle.
[0028] In some embodiments, the raised portions and the recessed portions may be arranged in multiple rows and columns with uniform spacing, or the arrangement may be adjusted according to actual needs, such as partially arranged in uniform spacing and partially arranged in non-uniform spacing.
[0029] In some embodiments, the thickness of the positive electrode sheet is recorded as H, and the depth of the recessed portion and / or the height of the raised portion is recorded as h. Figure 2 As shown, there is no specific limitation on the thickness of the positive electrode sheet, and it can be adaptively adjusted according to the specific type of battery and application scenario.
[0030] The depth of the recessed portion is 3 μm-100 μm, for example, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any point value in the range of the above two point values, preferably 5 μm-80 μm; and / or, the height of the protruding portion is 3 μm-100 μm, for example, 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any point value in the range of the above two point values, preferably 5 μm-80 μm. The "depth of the recessed portion" can be interpreted as the maximum vertical distance from the bottom end of the recessed portion close to the positive electrode current collector to the first surface of the positive electrode sheet, such as Figure 2 As shown in h, the “height of the protrusion” can be interpreted as the maximum vertical distance from the top of the protrusion away from the positive electrode current collector to the second surface of the positive electrode sheet.
[0031] In some embodiments, the average spacing between adjacent recessed portions or adjacent raised portions is recorded as d, and the average spacing between adjacent recessed portions (two adjacent recessed portions) is 0.5 mm-9 mm, for example, it can be 0.5 mm, 0.7 mm, 0.9 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or any point value in the range of the above two point values, preferably 1 mm-6 mm; and / or, the average spacing between adjacent raised portions (two adjacent raised portions) is 0.5 mm-9 mm, for example, it can be 0.5 mm, 0.7 mm, 0.9 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or any point value in the range of the above two point values, preferably 1 mm-6 mm. The average spacing between adjacent raised portions and the average spacing between adjacent recessed portions may be the same or different, preferably the same. The “average spacing between adjacent protrusions” or “average spacing between adjacent depressions” can be interpreted as the shortest straight distance between the center points of two adjacent protrusions or two adjacent depressions on the surface of the positive electrode sheet in the length direction of the positive electrode sheet, recorded as the average spacing between adjacent first protrusions or the average spacing between adjacent first depressions, such as Figure 2 As shown in middle d.
[0032] In some embodiments, the diameter of the concave portion or the convex portion is recorded as r, and the diameter of the concave portion is 0.2 mm-8 mm, for example, it can be 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm or any point value in the range of the above two point values, preferably 0.5 mm-4 mm; and / or, the diameter of the convex portion is 0.2 mm-8 mm, for example, it can be 0.2 mm, 0.4 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm or any point value in the range of the above two point values, preferably 0.5 mm-4 mm. The diameter of the convex portion and the diameter of the concave portion can be the same or different, preferably the same. The “diameter of the concave portion” can be interpreted as the maximum straight-line distance between the two edges of the concave portion in the direction parallel to the positive electrode sheet; the “diameter of the convex portion” can be interpreted as the maximum straight-line distance between the two edges of the convex portion in the direction parallel to the positive electrode sheet, such as Figure 2When the diameter of the concave portion and / or the convex portion meets the above range, the area of the concave portion can be controlled to avoid the weakening of the pole piece strength due to too large a diameter, which is prone to physical structural damage and causes the surface structure of the pole piece to break and the battery performance to deteriorate. It can also avoid the situation where the diameter is too small, the stress concentration of the pole piece is not significantly improved, and the electrolyte cannot penetrate the inside of the pole piece well, which does not significantly improve the fast charging performance of the battery.
[0033] In some embodiments, the mass proportion A of the boron-containing additive in the electrolyte satisfies: 0.1≤A≤1, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any point value in the range composed of any two of the above point values. The mass proportion of the boron-containing additive further satisfies the above range, which can better form a film at the negative electrode, and the formed SEI film is more stable, inhibiting the side reaction of the interface. At the same time, when there are too few boron-containing additives, the effect of inhibiting lithium precipitation is poor; when there are too many boron-containing additives, it is avoided that high-temperature gas production will be serious.
[0034] In some embodiments, the boron-containing additive includes at least one of lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF4), and tris(trimethylsilyl)borate (TMSB).
[0035] In some embodiments, the mass proportion B of fluoroethylene carbonate in the electrolyte satisfies: 8≤B≤20, for example, it can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any point value in the range composed of any two of the above points. When the mass proportion of fluoroethylene carbonate further satisfies the above range, it can continuously repair the SEI film structure and stabilize the silicon negative electrode interface during the cycle. When the mass proportion of fluoroethylene carbonate is too small, the SEI film structure is unstable, which easily leads to lithium precipitation and side reactions; when there is too much fluoroethylene carbonate, the gas production caused by the poor high temperature stability of ethylene carbonate is avoided.
[0036] In some embodiments, the battery includes a negative electrode sheet; the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon material; in the negative electrode active material, the mass proportion of silicon element is recorded as E%; the mass proportion of silicon element E satisfies: E satisfies: 0.5≤E≤30, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18, 20%, 22%, 24%, 26%, 28%, 30% or any point value in the range composed of any two of the above point values.
[0037] Although silicon materials have high lithium insertion capacity, they have a large volume expansion problem during the charging and discharging process, which will generate great stress inside the battery and squeeze the pole piece. With multiple cycles of charging and discharging, the pole piece is at risk of breaking, and the SEI film on the surface of the silicon material will be broken, resulting in uneven thickness of the SEI film on the surface of the negative electrode. In addition, the stress caused by volume expansion may also cause a decrease in the internal porosity of the battery, reduce the lithium ion migration channel, cause lithium metal precipitation, and affect battery safety. The present invention can provide a deformation space by setting a recessed portion on the positive electrode sheet, effectively alleviating the volume expansion problem during the cycle, thereby improving the fast charging performance and cycle stability of the battery. Boron-containing additives and fluoroethylene carbonate are introduced into the electrolyte. The two work together to improve the lithium insertion dynamics on the surface of the pole piece, reduce the lithium insertion tortuosity, and improve the thickness uniformity of the SEI film. Low charge transfer impedance and better pole piece wettability reduce the polarization of the surface area and internal area of the negative electrode sheet, making the silicon material more uniform in the deintercalation of lithium ions, thereby improving the fast charging performance and cycle performance of the battery and reducing the expansion of the battery cell.
[0038] Exemplarily, the test method for the content ratio of the silicon element can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions include: sample weight 5 mg, air as atmosphere, heating rate 10°C / min from room temperature to 900°C and constant temperature for 40 min. The relationship between the mass ratio of silicon-carbon material (denoted as x) and the final weight residual percentage of the entire test (denoted as y) is: x=7y / 15.
[0039] In some embodiments, A, B, and E satisfy the relationship: .
[0040] Boron-containing additives have a strong film-forming ability on the surface of silicon particles, and can generate SEI components containing boron organic matter, significantly reducing the impedance of the SEI film. Fluoroethylene carbonate can generate LIF and elastic polymers on the surface of the silicon negative electrode, which can effectively inhibit the side reactions at the interface and improve the thickness uniformity of the SEI film. When the boron-containing additives and fluoroethylene carbonate are used together, and the mass ratio of the negative electrode silicon element further satisfies the above relationship, the SEI film can be continuously repaired during the cycle, the side reactions at the interface can be inhibited, the interface stability can be further improved, and the membrane impedance can be reduced, the volume expansion of the negative electrode can be improved, and the battery cycle life and fast charging performance can be further improved. When the mass ratio of boron-containing additives and the mass ratio of fluoroethylene carbonate (A+B) are too small to satisfy the above formula, the film-forming effect of the negative electrode is not good, the membrane impedance is high, and the interface is unstable and prone to side reactions; and when the silicon element content E is too high to satisfy the above formula, the volume change of the silicon negative electrode during the charge and discharge process is more significant, the SEI film is unstable, and the rupture of the SEI film will lead to the continuous consumption of the electrolyte, thereby greatly affecting the cycle stability and performance of the battery.
[0041] In some embodiments, the silicon material includes at least one of silicon oxygen, silicon carbon, nano silicon, and silicon alloy.
[0042] In some embodiments, the electrolyte further comprises a nitrile additive, and the mass proportion of the nitrile additive is C% based on the total mass of the electrolyte; A, B and C satisfy the relationship: . Preferably, the mass proportion C of the nitrile additive in the electrolyte satisfies: 1≤C≤10, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range composed of the above two point values. Boron-containing additives and fluoroethylene carbonate have poor high-temperature stability and are prone to gasification under the catalysis of metal ions, while nitrile additives can complex positive electrode metal ions, further prevent metal ion dissolution, significantly improve high-temperature gas production, improve the stability of positive electrode materials, and improve the reduction of lithium insertion and separation rate caused by the rupture of active materials in the embossed parts, thereby improving the stability of the battery structure and improving the cycle stability of the battery. When the mass proportion C of nitrile additives further meets the above range, it can avoid the mass proportion of nitrile compounds being too large (C>10) to form an overly thick protective film on the surface of the positive electrode material to increase the resistance of the electrode, hinder the transmission of lithium ions, and cause the battery's charge and discharge performance to decrease; and avoid the mass proportion of nitrile compounds being too small (C<1) to complex positive electrode metal ions. The effect is not obvious and the problem of high-temperature gas production cannot be effectively improved.
[0043] In some embodiments, the nitrile additive includes a C2-C10 mononitrile compound and / or a C2-C10 polynitrile compound.
[0044] In some embodiments, the nitrile additive includes at least one of hexane trinitrile (HTCN), succinonitrile (SN), adiponitrile (AND), glutaronitrile (GN), ethylene glycol bis (propionitrile) ether (DENE), glycerol trinitrile (TCP), ethylene glycol bis (propionitrile) ether (DENE), glycerol trinitrile (TCP), trans-butylenedinitrile, and trans-hexenedinitrile. Further selecting the above nitrile additives can better improve high-temperature gas generation, improve the stability of the positive electrode material, and thus improve the stability of the battery structure and the cycle stability of the battery.
[0045] In some embodiments, the electrolyte includes C4-C8 carboxylic acid ester, and the mass proportion of C4-C8 carboxylic acid ester is recorded as D% based on the total mass of the electrolyte; C and D satisfy: . Preferably, the mass proportion D of C4-C8 carboxylates in the electrolyte satisfies: 3≤D≤60, for example, it can be 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any point value in the range composed of the above two point values, and it is further preferably 10≤D≤50. Since the nitrile additives have large interface impedance and high viscosity, the conductivity of the electrolyte will be reduced. The addition of a higher content of low-viscosity C4-C8 carboxylates in the electrolysis can avoid the increase in electrolyte viscosity caused by the addition of nitrile additives, and as the amount of nitrile additives added in the electrolyte increases, the amount of C4-C8 carboxylates added also increases accordingly, so that the electrolyte maintains a lower overall viscosity. At the same time, the further addition of C4-C8 carboxylates to the electrolyte, combined with the pore structure formed by the recessed portion of the negative electrode sheet, can also significantly improve the wettability of the electrolyte to the electrode sheet and enhance the fast charging performance of the battery.
[0046] In some embodiments, the C4-C8 carboxylic acid ester includes at least one of propyl propionate, ethyl propionate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, and propyl butyrate. Further selecting the above C4-C8 carboxylic acid ester can better reduce the viscosity of the electrolyte, further improve the conductivity of the electrolyte and the wettability to the electrode sheet, and enhance the fast charging performance of the battery.
[0047] In some embodiments, the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder. Preferably, the mass percentage of each component in the negative electrode active material layer is: 90wt%-99.4wt% of the negative electrode active material, 0.2wt%-5wt% of the conductive agent, and 0.4wt%-5wt% of the binder.
[0048] In some embodiments, the battery includes a positive electrode sheet, and the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode collector.
[0049] In some embodiments, the positive electrode active material layer includes a positive electrode active material, a conductive agent, and a binder. Preferably, the mass percentage of each component in the positive electrode active material layer is: 90wt%-99.4wt% of the positive electrode active material, 0.3wt%-5wt% of the conductive agent, and 0.3wt%-5wt% of the binder.
[0050] Exemplarily, the positive electrode active material is selected from one or more of transition metal lithium oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, and lithium-rich lithium manganese oxide; the chemical formula of the transition metal lithium oxide is Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0051] Exemplarily, the conductive agent includes, but is not limited to, one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.
[0052] Exemplarily, the binder includes, but is not limited to, one or more of styrene-butadiene rubber emulsion, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, and carboxylated chitosan.
[0053] In some embodiments, the lithium ion electrolyte further includes a lithium salt, which may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethyl sulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyl lithium or lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate (LiBF4), lithium bis(difluorophosphoryloxy)difluoroborate, and lithium tetrakis(difluorophosphoryloxy)borate. Based on the total mass of the electrolyte, the mass proportion of the lithium salt is 12.5%-25%, for example, it can be 12.5%, 15%, 18%, 20%, 22%, 24%, 25% or any point value in the range formed by any two of the above points. Adding lithium salts that meet the above range to the electrolyte can improve the ion conductivity of the electrolyte, improve the charge and discharge efficiency of the battery, and improve the fast charging performance of the battery.
[0054] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0056] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0057] Example 1-1 (1) Preparation of positive electrode The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), and acetylene black are mixed in a weight ratio of 97:2:1, and N-methylpyrrolidone (NMP) is added. The mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil with a thickness of 9 μm, and the coated aluminum foil is dried, and then rolled and cut to obtain a positive electrode sheet with a single-sided thickness of 54.5 μm and a double-layer thickness of 100 μm, wherein the single-sided thickness and double-layer thickness of the positive electrode active material layer both include the thickness of the aluminum foil. The cut positive electrode sheet is embossed with a special roller containing a convex portion, and the depth of the concave portion is 30 μm, the spacing between the concave portions is 2 mm, and the diameter of the concave portion is 2 mm.
[0058] (2) Negative electrode preparation Graphite and silicon-carbon material (the mass of silicon-carbon material accounts for 15% of the total mass of negative electrode active materials, and the mass of silicon element in negative electrode active materials accounts for 7.5%), single-walled carbon nanotubes (SWCNT), conductive carbon black (SP), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are made into slurry by wet process in the ratio of 97:0.5:0.5:1.5:0.5, and coated on both sides of the negative electrode current collector copper foil (thickness is 6 μm), and dried at 85°C for 5 h, rolled and die-cut to obtain the negative electrode sheet with a total thickness of 90 μm.
[0059] (3) Preparation of electrolyte In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), first mix the solvents ethylene carbonate (EC) and propylene carbonate (PC) in a mass ratio of 1:1, quickly add fully dried lithium hexafluorophosphate (LiPF6), shake well, add lithium difluorooxalatoborate (LiDFOB), fluoroethylene carbonate (FEC), nitrile compounds and C4-C8 carboxylates, and stir well to obtain the desired electrolyte. Among them, based on the total mass of the electrolyte, the mass proportion of LiDFOB is 1%, the mass proportion of FEC is 15%, the mass proportion of LiPF6 is 15%, the total mass proportion of nitrile compounds is 4%, and the total mass proportion of C4-C8 carboxylates is 15%. Among them, the nitrile compound is specifically a combination of succinonitrile (SN), adiponitrile (ADN), and 1,3,6-hexanetrinitrile (HTCN), and the mass ratio of the three is 2:2:5; the C4-C8 carboxylic acid ester is specifically a combination of propyl propionate (PP) and ethyl propionate (EP), and the mass ratio of the two is 16:5. The mass proportion of EC and PC in the electrolyte can be obtained by calculation.
[0060] (4) Preparation of diaphragm A composite layer of titanium oxide and polyvinylidene fluoride-hexafluoropropylene copolymer is coated on the polyethylene diaphragm.
[0061] (5) Preparation of lithium-ion batteries The positive electrode sheet, separator and negative electrode sheet prepared above are wound to obtain a bare battery cell without liquid injection; the bare battery cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare battery cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, the required lithium-ion battery is obtained.
[0062] Performance Testing (i) 25℃ Cyclic Performance Test The batteries prepared in the embodiments and comparative examples were charged and discharged for 800 cycles at 25°C according to a 3C step charge rate within the charge and discharge cut-off voltage range (3.0V-4.55V). The discharge capacity in the first week of the test was x1 mAh, and the thickness of the test battery was y1; the discharge capacity in the 800th week was x2 mAh, and the thickness of the battery after the 800th week was y2; the cycle capacity retention rate at the 800th week was R1=x2 / x1; and the battery thickness expansion rate at the 800th week was H1=(y2-y1) / y1.
[0063] (ii) 85℃ storage performance test First, the battery prepared by the embodiment and comparative example after the capacity is placed for 10 minutes, then discharged at 0.2C to 3.0V, placed for 10 minutes, and then fully charged at 0.5C (upper limit voltage 4.55V), cut off at 0.05C, placed for 10 minutes, and tested at 25℃±5℃ for voltage, internal resistance, and thickness y3 in the fully charged state; after the fully charged battery is placed in an 85℃ oven for 6 hours, the hot battery is taken out to test voltage, internal resistance, thickness y4, and capacity retention and recovery tests are performed, the initial capacity is recorded as x3, and the residual capacity is recorded as x4. Thickness expansion rate H2=(y4-y3) / y3; capacity retention rate R2=x4 / x3 (iii) 130℃ furnace temperature safety performance test The batteries prepared in the embodiments and comparative examples after capacity division were charged at 0.5C to the upper cut-off voltage (4.55V), and the voltage was kept constant at 0.05C. The fully charged samples were placed in a thermal shock test box at an ambient temperature of 25°C±5°C, and then the temperature was raised to 130°C±2°C at a rate of 15°C±2°C / min, and the test was terminated after maintaining this temperature for 60 min. The battery was observed to see whether it caught fire or exploded. If it did not catch fire or explode, the safety performance was indicated as "passed"; if it only caught fire, only exploded, or both caught fire and exploded, the safety performance was indicated as "failed", and the pass rate of the furnace temperature safety performance test was recorded.
[0064] (iv) Battery fast charging performance test The battery prepared in the embodiment and the comparative example was placed at a temperature of 25°C ± 5°C, and the sample status including voltage, internal resistance and thickness were tested; then the following steps were performed: 1) Standing for 10 min; 2) Discharging at 0.2C to the lower limit voltage; 3) Standing for 10 min; 4) Charging to the upper limit voltage at a specific rate (charging rate is as follows: 1C / 2C / 3C / 4C), with a cut-off current of 0.025C; 5) Standing for 10 min; 6) Discharging at 0.2C to the lower limit voltage; 7) Standing for 10 min; then looping steps 4-7 until all rate charging tests are completed. Compare the constant current charging ratio at each rate to evaluate the fast charging performance; the definition of constant current charging ratio: the ratio of the capacity of constant current charging at each rate to the capacity of constant current constant voltage charging, where the constant current charging ratio at 4C rate is used as the performance test result.
[0065] (v) Lithium deposition of the negative electrode of the battery The batteries prepared in the examples and comparative examples were subjected to a room temperature lithium deposition test, and the specific method is as follows: at 25°C, the charging process is: first charging to 4.55V at 3C constant current, and then charging at constant voltage until the current drops to 0.05C; the discharging process is: discharging to 3.0V at 1C constant current; finally charging to 4.55V at 3C, and then cutting off at 0.05C; after repeating 20 cycles, the battery is disassembled to observe the lithium deposition of the negative electrode sheet. The order of lithium deposition from light to heavy is no lithium deposition, slight lithium deposition, lithium deposition, and severe lithium deposition.
[0066] The Example 1-3 group and the comparative example 1-5 are carried out with reference to the Example 1-1, and the main differences are shown in Table 1. Among them, the Example 1 group is the change of the value of L (L=h / H). The Example 2 group is the change of the mass proportion (A) of the boron-containing additives in the electrolyte. The Example 3 group is the change of the mass proportion (B) of fluoroethylene carbonate (FEC) in the electrolyte. For the comparative example 1, the L value is too small and is not within the protection range. For the comparative example 2, the L value is too large and is not within the protection range. For the comparative example 3, the mass proportion of FEC is too small and does not meet the formula range. For the comparative example 4, the electrode is not embossed. For the comparative example 5, L, A, and B are all within the protection range, but do not meet the formula range.
[0067] Table 1 Note: “ / ” indicates the corresponding parameter of the measurement.
[0068] The present invention adopts embossing treatment on the positive electrode sheet, and adjusts the ratio L of the depth (h) of the concave part in the positive electrode sheet to the thickness (H) of the positive electrode sheet within the protection scope of the present invention, which can improve the stress concentration of the positive electrode, improve the structural stability of the positive electrode active material inside the positive electrode sheet and the electrolyte wettability. When the mass proportion (A) of the boron-containing additive in the electrolyte and the mass proportion (B) of the fluoroethylene carbonate are further adjusted to meet A+B≥0.15L+7, the non-uniformity of the thickness of the negative electrode SEI film caused by the inconsistent lithium insertion and delithiation rates of the positive electrode active particles due to the embossing treatment of the electrode sheet can be alleviated, the interface impedance can be reduced, the interface lithium precipitation can be improved, and the safety performance of the battery can be improved.
[0069] The Example 4 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 2. Among them, the Example 4 group changed the mass ratio (E) of the silicon element in the negative electrode active material.
[0070] Table 2 The present invention can provide deformation space by arranging a recessed portion on the positive electrode sheet, alleviate the volume expansion of the silicon-containing negative electrode during the cycle process, improve the fast charging performance and cycle performance of the battery, and reduce the expansion of the battery cell.
[0071] Example 5 was carried out with reference to Example 1-1, and the main differences are shown in Table 3. In Example 5, the total mass proportion (C) of nitrile compounds in the electrolyte was further changed.
[0072] Table 3 The present invention adds nitrile compounds to the electrolyte and adjusts the proportion of the nitrile compounds in the electrolyte to satisfy the above relationship with the mass proportion of the boron-containing additive and the mass proportion of fluoroethylene carbonate. This can improve the reduction in the rate of lithium insertion and separation caused by the rupture of the active material at the embossed part, thereby improving the structural stability of the battery and enhancing the cycle stability of the battery.
[0073] Example 6 was carried out with reference to Example 1-1, and the main differences are shown in Table 4. In Example 6, the total mass proportion (D) of C4-C8 carboxylic acid esters in the electrolyte was further changed.
[0074] Table 4 The present invention adds C4-C8 carboxylic acid esters to the electrolyte and adjusts the mass ratio of C4-C8 carboxylic acid esters in the electrolyte. When the mass ratio of the C4-C8 carboxylic acid esters and the nitrile compounds satisfy the above relationship, the viscosity of the electrolyte can be reduced, so that the electrolyte maintains a relatively low overall viscosity. At the same time, the addition of C4-C8 carboxylic acid esters to the electrolyte, combined with the pore structure formed by the concave portion of the negative electrode sheet, can also significantly improve the wettability of the electrolyte to the electrode sheet and enhance the fast charging performance of the battery.
[0075] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on at least one side surface of the positive electrode current collector; In the thickness direction of the positive electrode sheet, the positive electrode sheet comprises a first surface and a second surface arranged opposite to each other, and at least a part of the first surface is recessed toward the second surface to form a plurality of recessed portions; and / or at least a part of the second surface is recessed toward the first surface to form a plurality of recessed portions; Wherein, the thickness of the positive electrode sheet is recorded as H μm, the depth of the recess is recorded as h μm, L=h / H, L=5%~30%; The electrolyte includes a boron-containing additive, and the mass proportion of the boron-containing additive is denoted as A% based on the total mass of the electrolyte; The electrolyte includes fluoroethylene carbonate, and the mass proportion of fluoroethylene carbonate is denoted as B% based on the total mass of the electrolyte; L, A and B satisfy the relationship: A+B≥0.15L+7.
2. The battery according to claim 1, characterized in that A satisfies: 0.1≤A≤1; And / or, B satisfies: 8≤B≤20; And / or, the boron-containing additive includes at least one of lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium tetrafluoroborate, and tris(trimethylsilyl)borate.
3. The battery according to claim 1, characterized in that The electrolyte further comprises a nitrile additive, and the mass proportion of the nitrile additive is C % based on the total mass of the electrolyte, where C satisfies: 1≤C≤10; A, B and C satisfy the relationship: ; The nitrile additives include C2-C10 mononitrile compounds and / or C2-C10 polynitrile compounds.
4. The battery according to claim 3, characterized in that The nitrile additive includes at least one of hexanetrinitrile, succinonitrile, adiponitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, glycerol trinitrile, ethylene glycol bis(propionitrile) ether, glycerol trinitrile, trans-butenedinitrile, and trans-hexenedinitrile.
5. The battery according to claim 3, characterized in that The electrolyte includes C4-C8 carboxylic acid ester, and the mass proportion of C4-C8 carboxylic acid ester is recorded as D% based on the total mass of the electrolyte; D satisfies: 3≤D≤60; C and D meet the following requirements: .
6. The battery according to claim 5, characterized in that The C4-C8 carboxylic acid ester includes at least one of propyl propionate, ethyl propionate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, and propyl butyrate.
7. The battery according to any one of claims 1 to 6, characterized in that: The battery comprises a negative electrode sheet; the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises a silicon material; in the negative electrode active material, the mass proportion of silicon element is recorded as E%; and E satisfies: 0.5≤E≤30.
8. The battery according to claim 7, characterized in that A, B and E satisfy: ; And / or, the silicon material includes at least one of silicon oxygen, silicon carbon, nano silicon, and silicon alloy.
9. The battery according to any one of claims 1 to 6, characterized in that: In the thickness direction of the positive electrode sheet, a plurality of recessed portions are arranged at intervals in at least a portion of the first surface, and a plurality of raised portions are arranged correspondingly on the second surface; and / or a plurality of recessed portions are arranged at intervals in at least a portion of the second surface, and a plurality of raised portions are arranged correspondingly on the first surface; The spacing between the recessed portion and / or the raised portion is 0.5 mm to 9 mm; The diameter of the recessed portion and / or the raised portion is 0.2 mm to 8 mm; The depth of the concave portion is 3 μm-100 μm; and / or the height of the convex portion is 3 μm-100 μm.
10. The battery according to claim 9, characterized in that The spacing between the recessed portion and / or the raised portion is 1 mm to 6 mm; The diameter of the recessed portion and / or the raised portion is 0.5 mm to 4 mm; The depth of the concave portion is 5 μm-80 μm; and / or the height of the convex portion is 5 μm-80 μm.
Citation Information
Patent Citations
Pole piece and battery cell
CN107681116A
High-energy density lithium ion battery and electrolyte thereof
CN108598488A
Lithium ion battery electrolyte and high-energy-density lithium ion battery using same
CN109659614A
Negative electrode, and secondary battery
JP2009266718A
